Report of Repatriation Committee - Gregory, Holman
1937-10-26 039-0053-004 4 the disembarking of the said children at Bilbao take part in the handing over of the said children to their parents, relations or guardians and should afterwards agree with the Representatives of the said de facto government and the said Apostolic Delegate the order and the names of the children thereafter to be embarked in England for return to Bilbao. LASTLY we desire to express our gratitude to all those who have appeared before us for the assistance they have so readily rendered to us, and also to record our appreciation of the sustained efforts and work of our Secretary who has performed the duties of his office to the complete satisfaction of everyone interested in the issues before us. IN WITNESS whereof we have appended our signatures this 26th day of October, 1937. HOLMAN GREGORY. THEOBALD MATHEW. RICHD. R. LUDLOW. 292/946/39/53(iv)